Religious Tourism and Pilgrimage: Bibliometric Overview - Durán-Sánchez, Amador (Religions, 2018)
This paper reviews the academic literature related to religious tourism through a bibliometric study and citations of articles indexed in the multidisciplinary database Web of Science (WoS). Through an advanced search by terms, a representative set of 103 documents that form the ad-hoc basis of the analysis were selected. In view of the results, it is concluded that the United States is at the forefront of research, with almost 20% of the articles affiliated to one of its centres, mainly university centres. Publications on religious tourism are currently in an exponential growth stage, supported by the annual increase in the number of citations received. These papers are published in a small number of journals well positioned in their JCR category, classified within the field of Social Sciences Research.